Hacksaw: Hardware-Centric Kernel Debloating via Device Inventory and Dependency Analysis - Hu, Zhenghao; Lee, Sangho; Peinado, Marcus (30th ACM Conference on Computer and Communications Security (CCS 2023), 2023)
Kernel debloating is a practical mechanism to mitigate the security problems of the operating system kernel by reducing its attack surface. Existing kernel debloating mechanisms focus on specializing a kernel to run a target application based on its dynamic traces collected in the past - they remove functions from the kernel which are not used by the application according to the traces. However, since the dynamic traces do not ensure full coverage, false removals of required functions are unavoidable. This paper proposes Hacksaw, a novel mechanism to debloat a kernel for a target machine based on its hardware device inventory. Hacksaw accurately debloats a kernel without false removals because figuring out which hardware components are attached to the machine as well as which device drivers manage them is comprehensive and deterministic. Hacksaw removes not only inoperative device drivers that do not control any attached hardware components but also other kernel modules and functions which are associated with the inoperative drivers according to three dependency analysis approaches: call-graph, driver-model, and compilation-unit analyses. Our evaluation shows that Hacksaw effectively removes inoperative kernel modules and functions (i.e., their respective reduction ratios are 45% and 30% on average) while ensuring validity and compatibility.